1987
DOI: 10.3171/jns.1987.66.2.0293
|View full text |Cite
|
Sign up to set email alerts
|

A posttraumatic lumbar spinal synovial cyst

Abstract: A patient with posttraumatic lumbar radicular paresthesias is presented. The preoperative diagnosis of an epidural synovial cyst was considered. At surgery, an epidural synovial microcystic mass was found emanating from a distracted L4-5 facet joint and dissecting into the layers of the ligamentum flavum. A brief review of the condition is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 22 publications
0
39
1
Order By: Relevance
“…On occasion, it may be located on the dorsal aspect of the facets and extend into the soft paravertebral tissues; in this event there are either no symptoms [31,45] or just low-back pain [2,40]. In one case the cyst is described as developing entirely within the ligamentum flavum, dissecting the fibers inside it [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On occasion, it may be located on the dorsal aspect of the facets and extend into the soft paravertebral tissues; in this event there are either no symptoms [31,45] or just low-back pain [2,40]. In one case the cyst is described as developing entirely within the ligamentum flavum, dissecting the fibers inside it [16].…”
Section: Discussionmentioning
confidence: 99%
“…In the lumbar spine 220 cases have been described [1,2,16,21,28,34,38,40,43,45,48,51,[54][55][56]60].…”
Section: Introductionmentioning
confidence: 99%
“…Trauma is the next most common cause of the extradural lumbar spinal cyst. 10,14,18) Only one of our patients had a history of trauma after a recent accidental fall.…”
mentioning
confidence: 99%
“…Our patient was unusually young and, based on other reports describing the mechanism of excess stress such as motion and direct trauma, [2,7,18], the clinical history suggested that sport-(football-) related overactivity possibly caused partial distraction and injury of the left L4-5 facet joint, herniation of the synovial lining into the adjacent ligamentum flavum, and gradual proliferation and expansion of the cystic element by accumulation of viscous synovial fluid with acute haemorrhage, resulting in neurological symptoms.…”
Section: Yasuhisa Maezawa Hisatoshi Baba Kenzo Uchida Nobuaki Furusawmentioning
confidence: 99%
“…The majority of such cysts require surgical resection due to persistent radicular symptom and/or occasional pareses. [2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. We report an unusual young patient in whom a symptomatic intraspinal juxta-articular cyst showed spontaneous remission through cessation of sport activity and immobilisation of the lumbar spine.…”
Section: Introductionmentioning
confidence: 99%